KUALITAS PELAYANAN FRONT OFFICE, HOUSEKEEPING DAN FOOD AND BEVERAGE TERHADAP LOYALITAS TAMU MELALUI KEPUASAN - Surodjo Surodjo; Gendro Wiyono (Universitas Sarjanawiyata Tamansiswa, 2017)
This research aims to know the servqual (service quality) Front Office, Housekeeping and Food and Beverage effect on customer satisfaction or guests staying at LPP Garden Hotel Yogyakarta. Samples taken in this study is 75 respondents randomly drawn from guests staying at LPP Garden Hotel. Analysis of the data in this study is Inferential analysis conducted based on the test results of structural models. From the analysis of the coefficient of determination (R ²), note that guest satisfaction influenced by servqual Front Office, Housekeeping and servqual Food and Beverage amounted to 51.30%, and the remaining 48.70% influenced by other factors not included in the model, whereas the coefficient parameter servqual Front Office, Housekeeping and servqual Food and Beverage simultaneously affect the satisfaction that is equal to 0.494, meaning that the higher the coefficient parameter close to the higher guest satisfaction. The t- test based on statistics showing that servqual Front Office, servqual Housekeeping and servqual Food and Beverage simultaneously significantly affect satisfaction where t-statistic 4.391> t-table 1.66, its mean that Hypothesis is accepted Keyword: Servqual (Service Quality), Satisfaction, loyalty